Quality performance measurements of ambulance services in East Coast, Malaysia - Ahmad, Siti Farah Fatihah (2016)
INTRODUCTION East Coast Region states in Malaysia consists of Kelantan, Terengganu and Pahang. Similar with other states in Malaysia, ambulance services in this region are mainly provided by the government under Ministry of Health (MOH) and Ministry of Education (MOE) in the hospital-based emergency medical system (EMS). The service plays a significant role in public to provide fast and efficient healthcare services in the field as well as inside the ambulance. Therefore, the quality of services must be achieved according to international standard. This study is focused on evaluating the current performance of ambulance service in East Coast, Malaysia based on ambulance response time, ambulance crash and patients complaints as well as identifying the factors affecting the ambulance response time and also ambulance crash. METHODOLOGY This study was a cross-sectional study to evaluate the quality performance measurements of ambulance service in East Coast Region, Malaysia from January 2014 toDecember 2014. The data was obtained from questionnaires which was distributed to all the government hospitals in Kelantan, Terengganu and Pahang. Series of interviews with paramedics in-charged of ambulance services was done in selected hospitals to identify the factors contributed to its performance. It was conducted from November 2014 to March 2015. Statistical analysis was done using SPSS software version 22.0. Simple linear regression was used to determine the associated factors influencing the ambulance response time whereas simple logistic regression was used to determine factors associated with ambulance crash incident. RESULTS Total of 22 hospitals out of 26 were involved in this study with 8 hospitals from Pahang, 8 hospitals from Kelantan and 6 hospitals from Terengganu. Majority ambulances were in charged by assistant medical officer (pembantu pegawai perubatan) level U32 and above. Among parameters used to measure the key performance index, the ambulance response time had been the highest (95.5%). The mean response time in 2014 for all hospitals in East Coast, Malaysia was 16.90 minutes (SD) of 5.94. The mean ambulance crash was 0.77 and the median was 1.00. Majority hospitals had none /unknown complaints regarding ambulance services in their centres (59.1%). Otherwise, 40.9% had less that 10 formal complaints. From this study, univariate linear regression analysis showed that there were no significant factors influenced the ambulance response time and univariate logistic regression showed that there were no factors significantly associated with ambulance crash.CONCLUSION Based on the study, we concluded that the quality of ambulance services in East Coast, Malaysia still not achieving the international standard. There were no significant factors which influenced ambulance response time and ambulance crash.